Integrated genomic and transcriptomic analysis of polydactyly in chickens - Huang, Zhiying; Miao, Xiaomeng; Li, Diyan; Liu, Jia; Chen, Haolin; Su, Yuan (Frontiers in Veterinary Science, 2025)
IntroductionPolydactyly—the presence of extra digits—is a heritable limb anomaly observed in several chicken breeds. The Puan Panjiang black-bone chicken uniquely exhibits both four- and five-toed phenotypes, yet the genetic and transcriptional bases of this trait remain unclear. This study aimed to elucidate the genomic variants and gene expression changes underlying polydactyly in this breed.MethodsWe performed whole-genome resequencing (WGS) on 43 Puan Panjiang chickens (22 four-toed, 21 five-toed) and integrated publicly available data from 17 red junglefowl (RJF). After stringent quality filtering, we aligned reads to GRCg7b, identified high-confidence SNPs and InDels, and conducted sliding-window analyses of nucleotide diversity (θπ) and genetic differentiation (F ST) to detect selective sweeps. Concurrently, we carried out RNA-seq on embryonic foot tissues at days 6–9 (24 four-toed, 24 five-toed samples), quantified transcript levels (TPM), and identified differentially expressed genes (DEGs) with DESeq2 (adjusted P < 0.01, |log2FC|> 2). Fuzzy c-means clustering delineated temporal expression patterns, and enrichment analyses (KEGG, GO) characterized candidate pathways.ResultsGenomic scans revealed 1,339 and 1,035 positively selected genes in five-toed and four-toed chickens, respectively, with 335 shared loci relative to RJF. Top candidates in polydactylous birds included AUH, SEMA4D, and ROR2, while four-toed birds showed strong signals at RYR2, KITLG, and PGR. KEGG enrichment highlighted the MAPK signaling pathway in both groups, and uniquely in five-toed birds, lipid metabolism and vascular signaling pathways (e.g., sphingolipid and apelin signaling). Transcriptome profiling demonstrated that the greatest transcriptional divergence between phenotypes occurred at embryonic Days 8–9, pinpointing a critical window for extra-digit differentiation. Clustering analyses indicated coordinated regulation of genes involved in ribosome biogenesis, extracellular matrix organization, and muscle development across stages.DiscussionOur integrated analyses pinpoint MAPK pathway genes and lipid-vascular interactions as central to extra-toe formation, with the Days 8–9 embryonic window being pivotal. These findings offer clear targets for functional validation and may guide selective breeding for limb traits in poultry.